2011
DOI: 10.5402/2011/597350
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Malacoplakia in Children: Case Report

Abstract: Malacoplakia is a form of chronic granulomatous inflammatory reaction that rarely affects the pediatric age group. The gastrointestinal system is the second most common site for the occurrence of malacoplakia. We report the case of a 9-year-old girl who was hospitalized for abdominal pain, chronic diarrhea, and rectal hemorrhage. The endoscopic examinations and histopathology confirmed the diagnosis of intestinal malacoplakia. We successfully treated her with oral levofloxacin. This disease does not have any s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
6
0
2
Order By: Relevance
“…Genellikle beşinci ve yedinci dekatlar arasında ve kadınlarda daha sık görüldüğü bildirilmektedir. Bununla birlikte literatürde dokuz yaşında intestinal malakoplaki olgusu rapor edilmiştir (1,4 …”
Section: Discussionunclassified
See 1 more Smart Citation
“…Genellikle beşinci ve yedinci dekatlar arasında ve kadınlarda daha sık görüldüğü bildirilmektedir. Bununla birlikte literatürde dokuz yaşında intestinal malakoplaki olgusu rapor edilmiştir (1,4 …”
Section: Discussionunclassified
“…İlk kez 1902 yılında Michaelis ve Gutmann tarafından tanımlanmıştır (1). Daha sonra Von Hansemann "yumuşak plak" anlamına gelen malakoplaki ismini vermiştir (2).…”
Section: Introductionunclassified
“…The most accepted theory holds that chronic bacterial infections in patients with chronic weakness or immunosuppression would cause a deficit of cyclic guanosine monophosphate (cGMP) in microtubule and defective macrophage, causing them to phagocyte bacteria, but, in contrast, they would be unable to digest them due to intra-lisosomal failure. This situation would lead to intracytoplasmic deposition of fragments from bacteria, iron, and calcium, which would form the MG bodies (1,3,6,9) . In support of this theory, many studies state that these inclusions represent intake and persistence of bacteria in macrophages (4,5) .…”
Section: Vírus T-linfotrópico Humano Tipo I (Htlv-1) E Diagnóstico Dementioning
confidence: 99%
“…The gastrointestinal tract and retroperitoneal region are the secondary most affected sites (12%-15%) by the disease. Other locations are less affected such as brain, bone, lung, adrenal glands, thyroid, eyeball, among others (3,4,11) . Gupta et al reported, in 1972, the first case of pulmonary malakoplakia, which showed multiple nodules in lower lobe, simulating metastasis (5) .…”
Section: Vírus T-linfotrópico Humano Tipo I (Htlv-1) E Diagnóstico Dementioning
confidence: 99%
See 1 more Smart Citation